AVL-DRIVE pre-study report - Nybacka, Mikael; Holmlund, David; Danner, Christof (Luleå tekniska universitet, Innovation och Design, 2009)
This report present a pre-study project of AVL-DRIVE measurement system conducted from 27st of July 2009 until 15th of October 2009.The focus of the pre-study was to see how the system, as it is, could be used by the service providers and their customers during winter and summer testing in northern Sweden but also if the system could be extended and further developed to suit their needs. The AVL-DRIVE system is designed for objective assessment and quality control of Driveability based on human experience. Procedures for the objective assessment of the subjective perception of the driver have been used to define the evaluation method and formulas. Experiences acquired from internal and external vehicle benchmarks and Driveability development projects are incorporated in the AVL-DRIVE system. AVL-DRIVE uses different sensors and CAN bus information to capture the most significant data and vehicle parameters, such as, accelerations, engine data, vehicle speed, pedal position and vibrations. These input quantities are collected by the DMU2 (DRIVE Main Unit 2, located in the car boot) and passed on to a PC (Notebook, located at the passenger seat) for further analysis. Ratings for all Driving Modes are displayed online during driving. A rental car, Audi Q5 2.0 TFSI Quattro S-tronic, was equipped with the AVL-DRIVE system. The pre-study consisted of a number of tests, both on public roads including gravel and tarmac, but also on Bosch/ATM test tracks. One use for the system as it is today could be to study the change in vehicle drivability after endurance tests or after longer periods of testing. This could be done by driving a set of specified driving cycles called Fahr Manöver Katalog (FMK) in this report. Another idea put forward by an engineer at a service provider was to use the AVL-DRIVE system to compare certain driving maneuvers with a vehicle directly from the cold chambers and with the vehicle warmed up, to study the effects on Driveability for cold car and systems. Also these tests do not require any ESP, ...